Customer evaluation of factors affecting the use of credit cards at commercial banks - Luu, Phước Vẹn; Le, Minh Trí (Tạp Chí Khoa Học Và Công Nghệ Trường Đại Học Bình Dương, 2024)
This study shows the impact of factors on the use of credit cards by Vietnamese commercial banks through customer reviews. Data collected from a survey of 140 customers in An Giang was conducted through SPSS20 software. The study describes customer characteristics from the Theory of Planned Behavior (TPB). Research results show that customers' credit card use is affected by factors including card usage convenience, attitude, readiness of the banking system, perceived behavioral control, card usage costs and subjective norms. From there, the authors propose a number of solutions to promote the development of the current credit card market share.